MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN DIAGRAM VEE PADA MATERI LARUTAN PENYANGGA - Normita Elprianti; Iriani Bakti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstract. Has done research on the use of models guided inquiry in the learning material buffer solution. This study was aimed to (1) determine the activities of teachers, (2) determine the activities of students, (3) improve science process skills, (4) improve student learning outcomes and (5) evaluate the response of the students. The study design was a classroom action research (PTK) with two cycles. The subjects were students of class XI IPA 2 SMA Negeri 5 Banjarmasin with the number 38. The research instrument is a test and non test. The results showed that (1) the activities of teachers showed good category in the first cycle and excellent category in the second cycle, (2) the activity of students show category is active in the first cycle and the category of very active in the second cycle, (3) an increase in science process skills based on the results of the evaluation in the classical style of 65,78% in the first cycle to 89,47% in the second cycle and observations from the category of being the first cycle to the high category in the second cycle, (4) an increase in the thoroughness of the cognitive learning classical of 73,68% in the first cycle to 92,10% in the second cycle, an increase in affective learning outcomes of the category enough the first cycle to both categories at the second cycle, and increased psychomotor learning outcomes of the category enough the first cycle to both categories at the second cycle, (5) students responded positively to learning with guided inquiry model aided Vee diagram.Keywords: guided inquiry, Vee diagrams, buffers, science process skills, learning outcomes